ANALISIS GAYA BAHASA DAN NILAI MORAL PADA IKLAN LAYANAN MASYARAKAT DI SEPANJANG JALAN SOLO-NGAWI - Aulia Normalita (SALINGKA, 2020)
This study discusses the creativity of ad builders who produce ads in a style that is appealing in terms of the language, so that from those ads is able to bring out a style that is not only unique but also contains moral values that can educate Community. The research aims to describe the kinds of language styles and moral values in the public service advertisement along Solo-Ngawi road. This type of research is qualitative descriptive. Data collection techniques using document analysis techniques in the form of images, photographs and writings of advertisements found. The validity of the data uses theoretical triangulation techniques by matching some theories from existing data. Data matching results are found in accordance with Ratna's theory.  The results of the study were found an affirmation style of twenty data. Seventeen data is the moral value of ad type traffic. The style of language and moral value of community service ads, can be a reminder and a lesson for traffic and community users of the advertisements found.